The Gion Festival in Kyoto and Glocalization - Elisabetta Porcu (Religions, 2022)
The Gion Festival is a world-famous festival that takes place in Kyoto in July. It dates back to the Heian period (794–1185) and originated as a goryō-e ritual to placate departed spirits and disease-divinities. It is linked to the Yasaka Shrine, and it represents a great variety of religious and cultural influences. It is a complex and multidimensional event where issues of globalization can be seen at play at the local level. Against this background, this paper analyzes the Gion Festival as a religious and cultural phenomenon in relation to glocalization and the production of locality. In particular, it explores how the City of Kyoto represented the festival in connection with the 2030 United Nations Agenda for Sustainable Development, and the local–global interactions that relate to international tourism and global bureaucracy.